Comportamento biomecânico de materiais restauradores diretos em lesões cervicais não cariosas: análise por elementos finitos e revisão sistemática com meta-análise - Souza, André Mattos Brito de (2023)
Non-carious cervical lesions (NCCLs) are considered a pathology with a high incidence in the world population. The treatment of NCCLs is complex and must consider several factors, such as etiology, patient habits, presence of hypersensitivity, among others. When there is a need to replace lost mineral structures, the choice of restorative material can be an unknown, since the biomechanical characteristics can interfere in the duration and quality of the treatment. Therefore, the present work aimed to evaluate the influence of the physical properties of restorative materials on the retention and distribution of stress, in LCNCs of different sizes and formats. This study consists of two chapters, where the first aimed to compare the results of randomized clinical trials that evaluated the retention of two or more restorations in LCNCs with composite resin of different properties without the variable of the adhesive technique, in addition to analyzing through meta-analysis, the influence of viscosity on the longevity of restorations. A systematic review of the literature was carried out with 11 articles that met the inclusion criteria, which presented a low risk of bias in the presented methodology. The meta-analysis considered flow and viscous resins in 7 articles and showed no significant difference in retention between groups. The second chapter aimed to evaluate the biomechanical behavior of NCCLs of different depths (1, 1.5 and 2 mm) and formats (saucer and wedge) of upper premolars, restored with resin materials, when subjected to axial occlusal forces and oblique on the two cusps. For this, six materials with different characteristics were submitted to 3-point bending tests, microhardness and polymerization shrinkage to obtain their properties. In silico finite element tests simulated the distribution of forces and deformation in different regions. It can be observed that: the type of material directly interfered in the stress distribution; the appearance of a cavity permanently altered the behavior of the tooth under different efforts; and the association between modulus of elasticity and post-gel polymerization contraction was determinant for the difference in material behavior. The different strategies proposed in this study were effective to understand the influence of the physical properties of resin materials on the performance of the restoration.